If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 15 = x + 7 Reorder the terms: 15 + -1x = x + 7 Reorder the terms: 15 + -1x = 7 + x Solving 15 + -1x = 7 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 15 + -1x + -1x = 7 + x + -1x Combine like terms: -1x + -1x = -2x 15 + -2x = 7 + x + -1x Combine like terms: x + -1x = 0 15 + -2x = 7 + 0 15 + -2x = 7 Add '-15' to each side of the equation. 15 + -15 + -2x = 7 + -15 Combine like terms: 15 + -15 = 0 0 + -2x = 7 + -15 -2x = 7 + -15 Combine like terms: 7 + -15 = -8 -2x = -8 Divide each side by '-2'. x = 4 Simplifying x = 4
| 0.26=log*x | | d=15(30) | | 3x-13/4=2x | | 4(5x-5)=-3 | | (x-3.2)(x-3/2)=0 | | x+(x-7)+3(x-7)=63 | | 6n+19=63 | | 2443=x*.0625 | | 6x-15=x+10 | | 8p=63 | | x+(x+7)+3(x+7)=63 | | 2(t-1)=32+2t | | -ab=-bc | | -(6a+8)-5(a-7)= | | x+(3x)+(x+7)=63 | | gf(x)=70 | | ax=-bc | | -9(1-2y)=18y-9 | | p-22=-30 | | -(3x+5)=6x | | -20-5+x=x | | (x^2)+400=625 | | B+5=3b+9 | | 7x+48=x+48 | | 0.3(9.9)= | | e-34=681 | | 7x-17=2x | | 9x-32=x-56 | | sin60=.5/x | | b-160=23 | | 6(x-72)-4(x+64)=64-6(x-72) | | 7x-36=x+24 |